2007
DOI: 10.1080/00016340601124086
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum ultrasound in women with postpartum endometritis, after cesarean section and after manual evacuation of the placenta

Abstract: The ultrasonic findings in women with postpartum endometritis, after CS and after manual evacuation of the placenta, do not differ substantially from those during an uncomplicated puerperium. A delayed uterine involution process might explain the slight morphological differences observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 21 publications
1
28
1
2
Order By: Relevance
“…Understanding of normal view of the uterus during the entire period of puerperium helps practitioners to avoid unnecessary interventions for alleged retained products of conception (RPOC) or atonic uterus [68, 16]. During the normal puerperium period, the uterine involution is defined by the changing indices of the uterine size, the uterine cavity inserts, and the uterine artery flow [15, 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding of normal view of the uterus during the entire period of puerperium helps practitioners to avoid unnecessary interventions for alleged retained products of conception (RPOC) or atonic uterus [68, 16]. During the normal puerperium period, the uterine involution is defined by the changing indices of the uterine size, the uterine cavity inserts, and the uterine artery flow [15, 15].…”
Section: Discussionmentioning
confidence: 99%
“…The AP diameter was measured in two points: in the widest part of the longitudinal section and 5 cm below the uterine fundus (UF), perpendicular to the longitudinal uterine axis. As usual, in praxis, the measurements are performed in the widest (maximum) part of the uterus [35, 15–20]; however, some researchers suggest measuring 5 cm below the uterine fundus [1, 68]. This study compares both points of measurement in primiparous and multiparous patients.…”
Section: Methodsmentioning
confidence: 99%
“…There was not a significant increase in treatment failures amongst areas with a higher degree of Bacteroides fragilis resistance to clindamycin. 22 Once daily gentamicin (5 mg/kg every 24 h) dosing has been found more efficacious with comparable toxicity to traditional q8-hour dosing. b Parenteral therapy should be continued until the patient has been afebrile for 24-48 h, has normalized leukocyte count, and their pain is improving.…”
Section: Endometritismentioning
confidence: 99%
“…18 Empiric combination of clindamycin (900 mg q8 h IV or 600 mg q6 h IV) and an aminoglycoside (most commonly gentamicin 5 mg/kg q24 h or 1.5 mg/kg q8 h) remains the most effective regimen to treat postpartum endometritis. 22 A 2007 Cochrane review-republished in 2012-including 39 studies (n ¼ 4221 women) found clindamycin and gentamicin in combination to have equal or greater efficacy to other regimens including fluoroquinolones or regimens without coverage for Bacteroides fragilis (RR of 1.44 95% CI 1.15-1.80). There was not a significant increase in treatment failures amongst areas with a higher degree of Bacteroides fragilis resistance to clindamycin.…”
Section: Endometritismentioning
confidence: 99%
“…Sonographic imaging findings of endometritis are often nonspecific and may occasionally overlap with those of RPOCs, including increased endometrial stripe thickness and echogenicity with increased myometrial vascularity. 11,56 However, differentiation of these 2 entities is clinically relevant, as RPOCs are treated with dilation and curettage, whereas endometritis can be further complicated by dilation and curettage. Typically, endometritis presents with gas in the uterine cavity; however, this finding may be present in as many as 21% of healthy postpartum patients without complications for up to 3 weeks postpartum 11 ; therefore, correlation with clinical presentation and patient's signs and symptoms is essential.…”
Section: Puerperal Infections Endometritismentioning
confidence: 99%